Bio Efficacy of Bio Pesticides against Spotted Pod Borer (Maruca vitrata Geyer) Infesting Black Gram - Kumre, Anchal; Chaudhary, A. K.; Kumar, Pradeep; Gangwar, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study entitled “Bio-efficacy of bio-pesticides against spotted pod borer (Maruca vitrata Geyer) infesting black gram” at Organic Research Farm, Karguan Ji, Department of Entomology, Institute of Agricultural Sciences Bundelkhand University, Jhansi (U.P.) during kharif 2023 containing nine treatments viz, Neem oil 5%, Garlic bulb extract 5%, Bacillus thuringiensis 2.50 ml/l, Verticillium lecanii 5 ml/l, Panchagavya 10%, NSKE 5%, Castor oil 5%, Beauveria bassiana 5 ml/l and untreated control in RBD with three replications aiming to evaluate their efficacy of bio-pesticides against spotted pod borer. To evaluate the efficacy, two applications of treatments were carried out, and the spotted pod borer infestation on selected plants were evaluated after three, seven, and fourteen days after spraying. The outcomes showed that In the management of the spotted pod borer after the first and second spray, the Beauveria bassiana 5 ml/l (2.14) was superior and best effective in controlling larval population, followed by Bacillus thuringiensis 2.50 ml/l (2.34), and neem oil 5% (2.59), and the maximum yield 13.85 qt/ha and C: B ratio 1:1.71 was obtained from the Beauveria bassiana treated plot followed by Bacillus thuringiensis and neem oil by that obtained 12.89 qt/ha and 12.55 qt/ha yield, moreover 1:1.64 and 1:1.52 C: B ratio respectively.